Texto-caminho: a arte urbana como meio de comunicar narrativas de mulheres artistas de Fortaleza - Lemos, Aliria Aiara Duarte (2025)
This thesis aims to investigate the communicational possibilities enabled by urban art, with a particular focus on graffiti, created by women artists in the city of Fortaleza. In this study, I examine the artistic productions of four artists: Ceci Shiki and Bruna Beserra (members of Selo Coletivo, a collective of women in urban art), Alessandra Ribeiro (Dinha) and Raisa Christina. I therefore propose a study about urban art as a communication form, capable of stimulating a debate about its actions in the (literal and metaphorical) spaces of society, based on the narrative idea of a “texto-caminho” (path-writing), understanding research and life as an interconnected process. I use the concept of cartography (Barros; Kastrup, 2015; Passos; Barros, 2015; Rolnik, 2011), for the methodology of these writings, based on an inventive narrative, understanding that research happens during the process of doing. The study presents a historical analysis of urban art, with a focus on graffiti and its potential origins (Fonseca, 1981; Gitahy, 1999). Considering the engagement of these women in urban art and their contestation of urban space, I propose an intersectional approach (Akotirene, 2019; Crenshaw, 2002; Curiel, 2019), understanding gender as a behavior shaped in accordance with cultural and social norms (Butler, 2003), challenging the concept of fixed or predetermined identity (Rago, 2012). I also propose a closer look at urban art, particularly graffiti, specifically graffiti, as an inevitable, irreversible and unique form of communication (Santaella, 2011), capable of establishing symbolic mediations (Campos, 2007) both consciously and unconsciously (Sodré, 2014). In addition, it was possible to understand urban art, especially graffiti, as a great communicational power of artists in/for the city of Fortaleza.